Faktor-Faktor yang Mempengaruhi Ibu Hamil dalam Melakukan Perawatan Payudara di Klinik Pratama Nirmala Medan Tahun 2023 - Afnida Zahara; Isyos Sari Sembiring; Lidia Lesti Mastiur; Sri Ermaliani Br Bangun; Nuriani Nuriani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
A pregnant woman is a woman who carries a fetus in her womb after being fertilized BACKGROUND by spermatozoa. Pregnancy is a special situation for a woman as a prospective mother, because during pregnancy there will be physical changes that affect her life. During pregnancy, many changes will occur, both physical, social and mental. Pregnant mothers must have adequate nutrition, because the nutrition they get will be used for themselves and their fetus. For pregnant women, basically all nutrients require supplementation, but what is often lacking is protein energy and several minerals such as iron (Pantiawati in Mulyani, 2017). Breast care is a health behavior. Health behavior (according to Skinner) is: